Energy and momentum correction coefficients within contraction zone in open-channel combining flows - Jie Zhou; Cheng Zeng; Zhou Zhou; Ling-ling Wang; Yu-ran Yin (Water Science and Engineering, 2021)
Flow dynamics associated with open-channel confluences are highly three-dimensional (3D) with significant velocity gradients in the contraction zone downstream of junctions. The main objective of the present study was to investigate the impact of discharge ratio and junction angle on the non-uniformity of the velocity distribution within the contraction zone. A one-dimensional (1D) theoretical model and a 3D numerical model were developed to establish the relationships of the maximum values of energy and momentum correction coefficients (αm and βm) with discharge ratio (q) and junction angle (θ). The expressions of αm and βm were determined in terms of q and cosθ with the 1D theoretical model, and the constants were determined through regression analysis with the computed results from the 3D numerical model. The expressions show that αm and βm increased with an increase in junction angle or a decrease in discharge ratio due to the improved three-dimensionality of the flow structure. The expressions of αm and βm determined from the present study are consistent with the existing findings with θ = 90°.